GLOBALIZATION AND ITS IMPACT ON EDUCATIONAL PRACTICES: A SOCIOLOGICAL REVIEW OF CULTURAL INTEGRATION AND SOCIAL STRATIFICATION - Hikmat (GoAcademica Research dan Publishing, 2025)
Globalization has profoundly reshaped educational practices by fostering cross-cultural interactions and redefining the role of education in diverse societies. This article, based on a systematic literature review, examines how globalization influences cultural integration and social stratification within educational systems. The findings reveal that globalization encourages the diffusion of cultural values, yet simultaneously reinforces inequalities in access and outcomes. Literature suggests that educational institutions increasingly serve as arenas for negotiating cultural diversity, but persistent stratification often limits the inclusivity of such integration. Studies highlight that cultural integration within schools enhances intercultural competence, whereas social stratification perpetuates unequal opportunities among students. The review also indicates that globalization contributes to both homogenization and hybridization of educational practices, creating tensions between global standards and local identities. Comparative insights from various contexts demonstrate the uneven impact of globalization, with marginalized groups frequently experiencing systemic disadvantages. The synthesis emphasizes the sociological significance of understanding these dynamics in shaping equitable educational frameworks. The article contributes by bridging discussions on globalization, culture, and inequality, offering theoretical and practical implications for educational policy. It underscores the necessity of addressing stratification to realize the transformative potential of globalization in education.